2017
DOI: 10.1016/j.clinph.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Group III/IV locomotor muscle afferents alter motor cortical and corticospinal excitability and promote central fatigue during cycling exercise

Abstract: Objective To investigate the influence of group III/IV muscle afferents on the development of central fatigue and corticospinal excitability during exercise. Methods Fourteen males performed cycling-exercise both under control-conditions (CTRL) and with lumbar intrathecal fentanyl (FENT) impairing feedback from leg muscle afferents. Transcranial magnetic- and cervicomedullary stimulation was used to monitor cortical versus spinal excitability. Results While fentanyl-blockade during non-fatiguing cycling ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 66 publications
(94 reference statements)
10
141
5
1
Order By: Relevance
“…Since a decline in voluntary activation after exercise is indicative of a reduction in central motor drive to the muscles, available data does therefore not indicate that group III and IV muscle afferents inhibited central motor drive. However, a recent study suggests that decreased voluntary activation can be explained by inhibition of type III and IV afferents (Sidhu et al, 2017). Different levels of peripheral fatigue between trials (Neyroud et al, 2012; Amann et al, 2013; Johnson et al, 2015) without differences in voluntary activation are also incompatible with the critical peripheral fatigue threshold model of exercise regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Since a decline in voluntary activation after exercise is indicative of a reduction in central motor drive to the muscles, available data does therefore not indicate that group III and IV muscle afferents inhibited central motor drive. However, a recent study suggests that decreased voluntary activation can be explained by inhibition of type III and IV afferents (Sidhu et al, 2017). Different levels of peripheral fatigue between trials (Neyroud et al, 2012; Amann et al, 2013; Johnson et al, 2015) without differences in voluntary activation are also incompatible with the critical peripheral fatigue threshold model of exercise regulation.…”
Section: Discussionmentioning
confidence: 99%
“…At first sight, this would appear to be different from the findings in a resting muscle which suggest that the corticospinal pathway is depressed following fatiguing whole body exercise. However, in the presence of unchanged MEPs, CMEPs (amplitude and area) appear to be increased following exhaustive cycling (Sidhu et al, 2017) and fatiguing arm cycling sprints (Pearcey et al, 2016). Thus, in the limited number of studies testing motoneuronal excitability, motor cortical excitability was decreased which agrees with the outcome of the studies using a resting muscle to assess corticospinal excitability (Ross et al, 2010; Verin et al, 2004).…”
Section: Changes In Corticospinal Excitability From Before To After Fmentioning
confidence: 99%
“…Thus, in the limited number of studies testing motoneuronal excitability, motor cortical excitability was decreased which agrees with the outcome of the studies using a resting muscle to assess corticospinal excitability (Ross et al, 2010; Verin et al, 2004). Furthermore, the silent period following fatiguing whole body exercise has been reported to increase (Temesi et al, 2014), decrease (Temesi et al, 2013), or remain unchanged (Girard et al, 2013; Goodall et al, 2012; Jubeau et al, 2014; Sidhu et al, 2017; Thomas et al, 2015). It is important to note that in an unfatigued muscle, the duration of the silent period may directly be influenced by the size of the MEP.…”
Section: Changes In Corticospinal Excitability From Before To After Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous feedback from these muscle afferents is crucial for preventing premature fatigue as it has been shown that inhibition of group III and IV afferents (specifically non-nociceptive type, so called "ergoreceptors") during exercise in humans significantly compromised cardiac output, mean arterial blood pressure, femoral artery blood flow as well as pulmonary ventilation which ultimately resulted in arterial hypoxemia and metabolic acidosis [207,324]. On the other hand, group III/IV afferents have inhibitory effects on spinal motoneurons during intense exercise and with prolonged fatiguing exercise they also inhibit corticospinal drive, a phenomenon known as central fatigue (reduction of motor output) [325]. In addition, capsaicin-sensitive afferents have an inhibitory effect on the monosynaptic reflex [326] which constitutes a substantial component of total neural drive to the muscle during walking.…”
Section: Consideration Of the Physiological Role Of Group III And Iv mentioning
confidence: 99%